Clinicopathological and mutational analyses of colorectal cancer with mutations in the POLE gene. (25th June 2019) - Hino, Hitoshi; Shiomi, Akio; Kusuhara, Masatoshi; Kagawa, Hiroyasu; Yamakawa, Yushi; Hatakeyama, Keiichi; Kawabata, Takanori; Oishi, Takuma; Urakami, Kenichi; Nagashima, Takeshi; Kinugasa, Yusuke; Yamaguchi, Ken
Abstract: Here, we investigated the clinicopathological and mutation profiles of colorectal cancer (CRC) with POLE mutations. Whole‐exome sequencing was performed in 910 surgically resected primary CRCs. Tumors exceeding 500 counts of nonsynonymous single nucleotide variants (SNVs) were classified as hypermutators, whereas the remaining were classified as nonhypermutators. The hypermutators were subdivided into 2 groups. CRCs harboring more than 20% C‐to‐A and less than 3% C‐to‐G transversions were classified as POLE category tumors, whereas the remaining were classified as common‐hypermutators. Gene expression profiling (GEP) analysis was performed in 892 (98.0%) tumors. Fifty‐seven (6.3%) and 10 (1.1%) tumors were classified common‐hypermutators and POLE category tumors, respectively. POLE category tumors harbored a significantly higher SNV count than common‐hypermutators, and all POLE category tumors were associated with exonuclease domain mutations, such as P286R, F367C, V411L, and S297Y, in the POLE gene. Patients with POLE category tumors were significantly younger than those with nonhypermutators and common‐hypermutators. All POLE mutations in the early‐onset (age of onset ≤50 years old) POLE category (7 tumors) were P286R mutations. GEP analysis revealed that PD‐L1 and PD‐1 gene expression levels were significantly increased in both common‐hypermutators and POLE category tumors compared with those in nonhypermutators. CD8A expression was significantly upregulated in POLE category tumors compared with that in nonhypermutators. Thus, we concluded that CRCs with POLE proofreading deficiency had characteristics distinct from those of other CRCs. Analysis of POLE proofreading deficiency may be clinically significant for personalized management of CRCs. Abstract : The subset of patients with colorectal cancer harboring pathogenic exonuclease domain mutations in the POLE gene had an extremely high tumor mutation burden. These tumors had distinctive characteristics clinically and genetically.